Prevalence and factors associated with internet addiction among adolescents in Malaysia : a cross-sectional study - Ooi, Chor Yau; Siew, Mooi Ching; Norsiah, Ali; Shahnul, Kamal Hj Sidek; Azlin, Amat; Yusnita, Yatim; Zaiton, Yahya; Nabihah, Shamsuddin; Idora, Ibrahim; Fauzia, Abdul Majid; Fazlin Suhana, Othman; Nik Suhaila, Zakaria; et al. (JIACAM Publisher, 2020)
Background: Internet addiction (IA) among adolescents has become an important health problem due to its association with many negative consequences if not prevented early. However, there were no data on IA among adolescents in Malaysia.